THE IMPORTANCE OF A COMBINED 3D MODEL OF GROUND AND GEOTECHNICAL STRUCTURE - Ivan Vaníček; Daniel Jirásko (Acta Polytechnica CTU Proceedings, 2022)
The rapid progress of digitalisation in civil engineering is also happening in the branch of geotechnical engineering. BIM is a part of this process. The mutual connection of a 3D model of ground with a 3D model of geotechnical structure can help to give a clearer view of the interaction of this structure and ground. At the same time it also makes possible better control for all participants in the construction process, particularly if all conditions of this mutual interaction are fulfilled. There is considered whether the main aim of the construction process, namely that the care devoted to the individual phases of the structure design and execution actually correspond to the risk with which this structure and ground are indeed connected. Within this context a closer specification of the Eurocode 7 of the second generation will be identified , especially as it relates to different models.